RETRACTED : The Effect Of Motivation, Work Discipline And Work Environment On Employee Performance In Pt. Rekayasa Aplikasi Digital - Anisya Putri Firdaus; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science, 2024)
This study aims to determine and analyze employee motivation, discipline, and work environment and its effects on employee performance. This research was conducted at PT. Rekayasa Aplikasi Digital. In addition, this study aims to provide information and advice to the Human Resources Management of PT. Rekayasa Aplikasi Digital. Data was collected using a questionnaire with a Likert scale. The respondents in this study were 100 employees at PT. Rekayasa Aplikasi Digital itself. The analyses used in this study are quantitative descriptive analysis and qualitative analysis. The results showed that motivation, work discipline and work environment had a positive and significant effect on employee performance. This is shown from the coefficients table in the regression equation model KK = 0,261 M + 0,284 DK + 0,221 LK. The results of the conclusion of the hypothesis on the t-test partially obtained a significant value on the motivation variable of 0.05, while on the work discipline variable of 0.02 and on the work environment variable of 0.017. So it can be partially concluded that the three independent variables have a significant influence on the dependent variable.